Intelligent LED Lighting System - I. I. Maronchuk; I. V. Shirokov; A. A. Velchenko; V. I. Mironchuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article presents the development of an intelligent control system for LED lighting, applicable to autonomous electric lighting installations, outdoor lighting fixtures on posts to illuminate highways, roads, streets and surrounding areas. The system combines all local lighting systems in which the motion sensor and the LED luminaire are integrated into one network. Turning on the LED luminaire at reduced power is carried out automatically when the level of external natural light is less than a certain threshold value. In the case of appearance of an object moving along the motion sensors of neighboring local lighting systems, the speed and direction of movement of the object are determined. In accordance to the speed and direction of the object movement the number of local lighting systems is determined whose LED lamps should be switched on at a higher power and the appearance of the object at the next design point is predicted. The increase in the power of LED lamps is carried out smoothly when the object is approaching the corresponding local lighting system. Due to the dynamic control of the power of the LED luminaires, as moving objects appear in the coverage area of the intelligent lighting system, significant energy savings are achieved. Traffic safety conditions are increased, as the number of LED lamps operating with increased power is determined by the speed of the object, and its possible braking distance will be significantly less than the illuminated section of the roadway. Smooth changes in the power of LED lamps reduce the pressure on the driver of the vehicle. The choice of the motion sensor based on the autodyne radio blocking, which detects moving objects in a given sector of the controlled space, regardless of the time of day and weather conditions, is grounded.